La definición de "responsabilidad social empresaria" como tarea filosófica - Preziosa, María Marta (2005)
This study is a metaphysical essay defining Corporate Social Responsibility (CSR), through a series of Business Ethics texts covering the subject. The selected texts are written by Argentinean and Spanish authors rooted in the Social Teaching of the Church. The objective is to search the foundation of CSR as a moral obligation. The study begins with a logical approach, followed by a metaphysical one before engaging in ethical aspects. The meaning of «responsibility» and «CSR» concepts are defined. Regarding the concept’s metaphysical approach, the study is framed under Aristotelian categories of relationship and quality. From an ethical point of view, CSR is understood as a component of justice as virtue, and what specifically characterizes it is the acknowledgement of one’s own concurrence in the growth and development of the company’s relationship with its stakeholders. The question is posed whether the company, as such, acts in a moral manner –parallel to personal moral agency—. A delimitation of CSR actions is proposed.